Exploring the Correlation and Protective Role of Diabetes Mellitus in Aortic Aneurysm Disease - Arun, Divyatha; Munir, Wahaj; Schmitt, Lara Victoria; Vyas, Rohan; Ravindran, Jeuela Iris; Bashir, Mohamad; Williams, Ian Michael; Velayudhan, Bashi; Idhrees, Mohammed (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Diabetes mellitus is recognised as a significant risk factor for cardiovascular and peripheral vascular disease, as the abnormal metabolic state increases the risk for atherosclerosis, occlusive arterial disease and vascular dysfunction. There have been reports of potential association across the literature that illustrates a link between diabetes mellitus and aortic aneurysm, with the former having a protective role on the development of the latter. Methods: A thorough literature search was performed through electronic databases, to provide a comprehensive review of the study's reporting on the association of diabetes mellitus and aortic aneurysm, discussing the mechanisms that have been reported; furthemore, we reviewed the reports of the impact of oral hypoglycameic agents on aortic aneurysms. Results: Various proposed mechanisms are involved in this protective process including endothelial dysfunction, chronic hyperglycemia and insulin resistance. The evidence suggests a negative association between these disease process, with prevelance of diabetes mellitus resulting in lower rates of aortic aneurysm, via its protective mechanistic action. The increase in advanced glycation end products, increased arterial stiffness and vascular remodelling seen in diabetes, was found to have a profound impact on aneurysm development, its slow progression and lower rupture rate in these individuals. This review has also highlighted the role of oral hypoglycaemic agents having a protective effect against AA disease. Conclusion: A decrease in development, progression and mortality from aortic aneurysms as well as reduced rates of dissection, have been observed in those with diabetes. This review has provided a comprehensive insight on the effect of diabetes and its physiological processes, and elements of its con-committant treatment, having a protective role against these aortic diseases.